Trypsinized Placental Cell Cultures for the Propagation of Viruses and as “Feeder Layers” - Grogan, Elizabeth A. (1970)
The preparation and properties of cell cultures derived from human placental tissue are described and their usefulness for the propagation of animal viruses and as “feeder layers” is indicated.